Abdominal lymph node metastasis by lymphatic spread through the thoracic duct in patients with non‐small‐cell lung cancer. Issue 14 (25th May 2021) - Ryu, Wookyung; Lee, Myoung Kyu; Park, Mi Hwa; Hyun, In Young; Lee, Minkyung; No, Eun‐Ji; Yong, Seok Joong; Kim, Jung Soo; Lim, Jun Hyeok; Ryu, Jeong‐Seon
Abstract: Background: Abdominal lymph node metastasis (ALNM) is common in patients with metastatic non‐small‐cell lung cancer (NSCLC). However, its mechanism of spread remains to be elucidated. We investigated whether thoracic duct has the role as a pathway for ALNM in NSCLC using clinical data. Methods: We classified ALNM into subgroups by their location and evaluated its prevalence and association with clinical characteristics in 892 patients with metastatic NSCLC. The abdominal lymph nodes were classified into direct or indirect groups depending on whether they drain directly into the trunk (intestinal trunk or lumbar trunks) connected to the cisterna chyli. Results: One hundred‐five patients (11.8%) had ALNM. The paraaortic lymph node was most commonly involved, followed by the aortocaval, left gastric, paracaval, and celiac lymph nodes. After grouping the patients by location of ALNM, 56 patients (53.3%) with ALNM were in the "direct only" group, only seven patients (6.7%) were in the "indirect only" group, and 42 patients (40.0%) were in "both" groups. In patients whose intrathoracic lesions were limited to the right thorax, there was a significantly lower prevalence of ALNM (3.4% vs. 14.3%, p  < 0.001). On multivariate logistic regression analysis of clinical variables, higher N category was associated with increased risk of ALNM. Conclusions: This study suggests that the thoracic duct is one of the potential routes of lymphatic spread to the abdominal lymph nodes. Clinicians should assess for the presence of ALNM during staging work‐up and follow‐up for NSCLC patients with intrathoracic lesion in left thorax and with high N category. Abstract : ALNM was more common in the direct than indirect lymph nodes. ALNM was more common in patients with left thorax lesion compared to those with right thorax lesion only. ALNM risk was increased for patients with higher N category. These results indicate that ALNM occurs by lymphatic spread through the thoracic duct in patients with metastatic NSCLC.